Стратегічні імперативи функціонування, безпеки та повоєнного відновлення підприємств виробничої та аграрної сфер в умовах воєнних загроз та цифрових викликів - Семикіна, М. В.; Дмитришин, Б. В.; Бугаєва, М. В.; Semykina, M.; Dmytryshyn, B.; Buhaieva, M. (My University, 2026)
Статтю присвячено обґрунтуванню стратегічних пріоритетів у забезпеченні повоєнного відновлення підп-риємств реального сектору в умовах воєнних загроз та цифрових викликів. Розкрито специфіку функціонування виробничих та аграрних підприємств під час воєнного стану, визначено загрози. Обґрунтовано подвійну роль цифровізації: допомога у виживанні та адаптації бізнесу через хмарні сервіси, точне землеробство, автомати-зацію та одночасне створення нових ризиків – кіберзагроз та енергозалежності. Виділено галузеві відмінності в стратегіях безпеки: дистанційний захист земель та врожаю в агросекторі та контроль обладнання в проми-словості. Запропоновано концептуальне бачення повоєнного відновлення, засноване на чотирьох стратегічних імперативах: цифровій прозорості для залучення інвестицій, випереджальному управлінні ризиками, технологі-чній модернізації для енергетичної незалежності та розвитку цифрових компетенцій персоналу. The article is devoted to substantiating strategic priorities in ensuring resilience and qualitative recovery of domestic real sector enterprises under the simultaneous impact of military threats and global digital transformation. Based on systematization of scientific sources and practical experience, the specifics of manufacturing and agricultural enterprises during martial law are revealed, and critical changes in the security environment are identified. The dual role of digitalization is substantiated: assisting business survival and adaptation through cloud services, precision agriculture, and automation, while simultaneously creating new risks – cyber threats and energy dependency. Sectoral differences in security strategies are highlighted: remote protection of land and harvest in the agricultural sector versus equipment control and process continuity in manufacturing. A conceptual vision for post-war recovery is proposed, based on four strategic imperatives: digital transparency to attract investments, proactive risk management, technological modernization for energy independence, and development of personnel's digital competencies. The research demonstrates that digital transformation, despite associated vulnerabilities, becomes a crucial driver of business adaptation and competitive advantage during reconstruction. Particular attention is paid to the integration of physical security measures with cyber protection mechanisms, ensuring comprehensive economic security. The article substantiates that enterprises succeeding in post-war recovery will be those capable of simultaneously addressing infrastructure restoration, technological modernization, and personnel development. The proposed strategic framework enables transformation of wartime challenges into opportunities for business modernization during post-war reconstruction. Implementation of identified imperatives requires coordinated efforts in three directions: infrastructure investment, cybersecurity infrastructure development, and human capital enhancement. The findings contribute to understanding economic security mechanisms in crisis conditions and provide practical guidance for enterprise management strategies during wartime and reconstruction periods.
Strategic imperatives for functioning, security, and post-war recovery of manufacturing and agricultural enterprises under military threats and digital challenges
Keywords: економічна безпека; повоєнне відновлення; аграрний сектор; виробнича сфера; цифрові виклики; воєнний стан; стратегічні імперативи; цифрова трансформація; кібербезпека; управління ризиками; economic security; post-war recovery; agricultural sector; manufacturing sector; digital challenges; martial law; strategic imperatives; digital transformation; cybersecurity; risk management